PEMERIKSAAN KLINIK BERBASIS BIOSENSOR BAGIAN 2: Biosensor Virus Untuk Deteksi Penyakit Patogen - NUR HABIBAH (Meditory : The Journal of Medical Laboratory, 2016)
Nowadays, rapid determination of several viruses which caused pathogen diseases is really important. Most of rapid detection of human pathogen viruses was developed by using biosensor technology. Biosensor technology offers several advantages, such as simple, efficient, low cost, fast response, easy to operate, and reliable. Viral detection by using biosensor can also avoid the delay of diagnosis, so the doctor can determine the type of drugs quickly and also can decide the type of patient care, properly. Most of biosensor for virus detection was exploited by using electrochemical principle, with amperometric and volumetric transducer. Almost of virus biosensor used immobilized antibody onto electrode surface as a biorecognition element. Some of viruses that could be detected by using electrochemical biosensor are HCV, HBV, HIV and influenza virus. However, quality control of the biosensor result is important, so the biosensor could be selected as an alternative method for on-site determination, especially in clinical determination. Keywords: biosensor, virus biosensor, virus detection, pathogen diseases detection